2018
DOI: 10.3892/or.2018.6501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer agents using patient-derived tumor organoids characteristically similar to source tissues

Abstract: Patient-derived tumor xenograft models represent a promising preclinical cancer model that better replicates disease, compared with traditional cell culture; however, their use is low-throughput and costly. To overcome this limitation, patient-derived tumor organoids (PDOs) were established from human lung, ovarian and uterine tumor tissues, among others, to accurately and efficiently recapitulate the tissue architecture and function. PDOs were able to be cultured for >6 months, and formed cell clusters with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…In addition to this, our work highlighted metformin and mTOR inhibitors, such as everolimus, and they have already shown promise in early clinical trials for the treatment of EC [ 190 , 191 , 192 , 193 , 194 , 195 ]. In vitro studies have demonstrated the therapeutic benefit of AURKA inhibitors, cordycepin, genistein, suramin, sodium butyrate and ibrutinib [ 89 , 196 , 197 , 198 , 199 , 200 ]. The MEK inhibitor selumetinib has shown anti-tumour effects in EC cell culture [ 201 ], whilst binimetinib is yet to be studied in EC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, our work highlighted metformin and mTOR inhibitors, such as everolimus, and they have already shown promise in early clinical trials for the treatment of EC [ 190 , 191 , 192 , 193 , 194 , 195 ]. In vitro studies have demonstrated the therapeutic benefit of AURKA inhibitors, cordycepin, genistein, suramin, sodium butyrate and ibrutinib [ 89 , 196 , 197 , 198 , 199 , 200 ]. The MEK inhibitor selumetinib has shown anti-tumour effects in EC cell culture [ 201 ], whilst binimetinib is yet to be studied in EC.…”
Section: Discussionmentioning
confidence: 99%
“…There also is evidence for an antiproliferative role of ibrutinib in endometrial cancer. Tamura et al [43] created patient-derived tumor organoids (PDOs) from human tumor tissue (lung, ovarian, endometrial). The morphology, histology, and gene expression of these organoids were similar to their source tumor.…”
Section: Gynecological Malignanciesmentioning
confidence: 99%
“…In addition to benign endometrial organoid models, organoids have also been derived from endometrial cancer tissues, and used for drug testing. [65][66][67][68] These endometrial cancer organoids recapitulated genetic and phenotypic characteristics of endometrial tumors, and could be an efficient way of testing therapies. [66][67][68] Organoids have also been derived from the endometrium of patients with other diseases, including endometrial hyperplasia, Lynch syndrome, and endometriosis.…”
Section: Human Endometrial Organoids: Recapitulating Native Tissues Wmentioning
confidence: 99%
“…[65][66][67][68] These endometrial cancer organoids recapitulated genetic and phenotypic characteristics of endometrial tumors, and could be an efficient way of testing therapies. [66][67][68] Organoids have also been derived from the endometrium of patients with other diseases, including endometrial hyperplasia, Lynch syndrome, and endometriosis. 65 Endometrial organoids have provided an alternate physiologic model of the endometrium that can be adapted to biobanking, drug screenings, and investigation of endometrial physiology and pathology.…”
Section: Human Endometrial Organoids: Recapitulating Native Tissues Wmentioning
confidence: 99%